AN EXAMINATION OF ISTANBUL SCHOOLS OF THE SPATIAL REQUIREMENTS REQUIRED BY THE EDUCATIONAL MODEL APPLIED TO EIGHT-YEAR BASIC EDUCATION SCHOOL - Cinar, Candan; Cizmeci, Fusun; Akdemir, Zafer (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2007)
The study is made up of three main sections. In the first section the changes that primary education went through from the establishment of the Republic in Turkey until today have been examined with attention to the socio-economic and political conditions that the country was experiencing. In a later section of the study the conditions that show the spatial requirements of the primary schools are first set out with their priorities; then later how the educational buildings that experienced transformation in the primary education process were considered. In the last section of the study, the developmental period in the primary education system in general that is taken up separately in the first section was reduced to the particular characteristics of Istanbul province.
Keywords: primary education; spatial requirements; education buildings; public and private school; Architecture